Noteworthy - Lim, Phyllis L. (Thomson/Heinle, 2005)
Noteworthy is a high-intermediate level ESL/EFL listening and note-taking program with three major goals: to improve listening comprehension and develop academic note-taking skills through extensive practice; to provide international students with a deeper, clearer understanding of life and culture in the United States; to increase pproductive skills through tasks in which students use aural input for reproduction and transfer activities in speaking and writing.